ASSOCIATION BETWEEN OCCUPATIONAL NOISE EXPOSURE AND HYPERTENSION RISK: META ANALYSIS - Aurina Firda Kusuma Wardani; Siti Rachmawati; Anggreini Beta Citra Dewi (Journal of Vocational Health Studies, 2026)
Background: Noise is a common occupational physical hazard that, when esposure exceeds threshold limits, can elevate blood pressure. Work-related hypertension may affect workers’ productivity. Purpose: To conduct meta-analysis of the association between occupational noise exposure and the risk of high blood pressure. Review: The authors performed meta-analysis of 10 articles published between 2018-2023 from different sources, including Google Scholar, PubMed, and Science Direct. The terms "noise exposure" or "occupational noise" and "hypertension" and "multivariate analysis" were used to search for papers, which were then chosen based on inclusion and exclusion criteria. Review Manager (RevMan) 5.3 was used to analyze this study. Result: According to the findings of a meta-analysis of 10 publications, being exposed to noise at work raised one's risk of developing hypertension by a factor of 1.83 in comparison to not being exposed to it (aOR = 1.83; 95% CI = 1.49-2.24; p-value = 0.001). Conclusion: Working in a noisy environment increases the risk of high blood pressure.